A comunicação on-line e a face-a-face nos processos de liderança nas organizações corporativas - Proetti, Sidney (2004)
This dissertation demonstrates the study of organizational communication, more precisely about the use of online communication in leadership processes. After bibliographical research of deep intensity, a theoretical reference was built that documented fundamental themes for the formation of the reasoning about the central subject of the work. The work was structured in 6 chapters that are in the following order: Leadership, types of leaders and leadership process; The communication process; Internal organizational communication and online communication; Online communication and corporate society; The problem studied, the research questions and the methodology; And results and commented analysis of the research: the online communication in the leadership processes in Cia. Transnacional. The object of study, the problem that motivated the research was expressed as: "What are the consequences of online communication in interpersonal relationships between leaders and leaders in a corporate organization?" For this, we used qualitative and quantitative research with data collection through a research questionnaire formulated and sent online and with the answers received by the same means of communication. The chosen organization was a large company located in São Bernardo do Campo, state of São Paulo, which operates in the assembly of medium and large size automotive vehicles and is referenced in the dissertation under the pseudonym "Cia. ​​Transnacional" . The main objective of the study was to understand the consequences (effects) of the use of online communication by the leaders and, after identifying them, they were documented so that they contribute in a pedagogical and professional way to the global society that adopted the informatics in the environments. work. (AU)